Analysis of different substrates and methods for overcoming dormancy of Tectona grandis L.f. - Oliveira Xavier, Millena Oliveira Xavier; Oliveira Xavier, Millena Oliveira Xavier (Pubvet, 2021)
The objective was to evaluate the methods of overcoming dormancy in seeds of Tectona grandis L.f., (Teca), to verify their viability in uniform the seed germination. Five methods for overcoming dormancy were tested for each substrate, being them; Control (T1, T6); Seeds packed on a black canvas for 96 hours and submitted to an average temperature of 25 ° C (T2, T7); Immersion of the seeds in running water for 48 hours (T3, T8); Immersion of the seeds in water for 72 hours (T4, T9); Immersion of the seeds in water during the night and the day, placing them in the sun, on a plastic canvas, repeating the technique for three days and then placing the seeds in water for another 24 hours (T5, T10). Where the T1 to T5 treatments were used on the washed sand substrate, and the T6 to T10 treatments were used on the sand + organic soil substrate. The main parameters evaluated were: percentage of germination and germination speed index (IVG). The data were submitted to analysis of variance, and the means were compared using the Tukey test with a 5% significance level. The highest values of percentage of germination and IVG were obtained in treatments (T6) and (T7).